IAE PAN Centre for Research on ancient Technologies in Łódź - Maik, Jerzy (Polska Akademia Nauk. Wydział I Nauk Humanistycznych i Społecznych, 2013)
ill. ; 28 cm

"Textil- und Lederfunde der Grabung Feddersen Wierde", R. Ullemeyer, K. Tidow, "Einzeluntersuchungen zur Feddersen Wierde (Wagen, Textil- und Lederfunde, Bienenkorb, Schlackenanalysen", H. Hajen, R. Ullemeyer, K. Tidow, F. Ruttner, Wiesbaden 1981 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1983)
23 cm
Keywords: history of material culture

"Spätmittelalterliche und frühneuzeitliche Gewebefunde aus der Lübecker Innenstadt", K. Tidow, "Lübecker Schriften zur Archäologie und Kulturgeschichte", Bd. 4, Bonn 1980; "Textilfunde aus einem Brunnen vom Grundstück Schüsselbuden 16/Fischstrasse 1-3 in Lübeck", K. Tidow, "Lübecker Schriften zur Archäologie und Kulturgeschichte", Bd. 3, Bonn 1980 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1982)
23 cm
Keywords: history of material culture

"Die Wollweberi im 15. bis 17. Jahrhundert", K. Tidow, "Veröffentlichungen das Fördervereins Textilmuseum Neumünster e. V.", H. 6, Neumünster 1978; "Wollweber, Tuchmacher und Leinenweber im 17. und 18. Jahrhundert in Neumünster", "Veröffentlichungen das Fördervereins Textilmuseum Neumünster e. V.", H. 8, Neumünster 1981 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1984)
23 cm
Keywords: history of material culture

"Forhistoriske textiler i Skandinavien (Prehistoric Scandinavian Textiles)", Lise Bender Jørgensen, Nordiske Fortidsminder ser. B, Bind 9, København 1986 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1990)
23 cm
Keywords: history of material culture

"Lībiešu apgērbs 10.-13. gs.", Anna Zariņa, Rīga 1988 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1991)
23 cm
Keywords: history of material culture

"Historia europejskiego włókiennictwa odzieżowego od XIII do XVIII w.", Irena Turnau, Wrocław-Warszawa-Kraków-Gdańsk-Łódź 1987 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1988)
23 cm
Keywords: history of material culture

"Dress in Anglo-Saxon England", G. R. Owen-Crocker, Manchester 1986 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1988)
23 cm
Keywords: history of material culture

Wełna tkanin wykopaliskowych jako źródło do badań ras owiec - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2001)
ill. ; 23 cm
Keywords: history of material culture

La Draperie au Moyen Age. Essor d'une grande industrie européenne, Dominique Cardon, Paris 1999 : [recenzja] - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2001)
23 cm
Keywords: history of material culture

"Textiles and Clothing c. 1150 - c. 1450", E. Crowfoot, F. Pritchard, K. Staniland, [w:] "Medieval Finds from Excvavations in London", t. 4, London 1992 : [recenzja] - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 1995)
23 cm
Keywords: history of material culture

Kalisz - miasto lokacyjne w XIII-XVIII wieku. Studium archeologiczno-architektoniczne, Janusz Tomala, Kalisz 2004 : [recenzja] - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2004)
23 cm
Keywords: history of material culture

"Tejido y cesteria en la Peninsula Iberica. Historia de su técnica e industrias desde la Prehistoria hasta la romanización", Carme Alfaro Giner, Bibliotheca Praehistorica Hispana vol. XXI, Madrid 1984 : [recenzja] - Maik, Jerzy (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1989)
23 cm
Keywords: history of material culture

Textiles from Masada. A Preliminary Selection, A. Scheffer, H. Granger-Taylor, [w:] Masada IV. The Yiagael Yadin Excavations 1963-1965, Jerusalem 1994 : [recenzja] - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 1998)
23 cm
Keywords: history of material culture

Słownik terminologiczny włókiennictwa, Marta Michałowska, Biblioteka Muzealnictwa i Ochrony Zabytków, seria B tom 92, Warszawa 1995 : [recenzja] - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 1997)
23 cm
Keywords: history of material culture

"North European Textiles until AD 1000", Lise Bender Jørgensen, Aarhus 1992 : [recenzja] - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 1994)
23 cm
Keywords: history of material culture

Sukiennictwo w średniowiecznej Polsce - Maik, Jerzy (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2021)

Preface - Maik, Jerzy; Strzyż, Piotr (Institute of Archaeology and Ethnology of Polish Academy of Sciences, 2017)
29 cm
Keywords: archaeology -- journals; history -- journals

"Das alamanische Gräberfeld von Giengen an der Brenz (Kreis Heidenheim)", P. Paulsen, H. Schach-Dörges, Stuttgart 1978 : [recenzja] - Maik, Jerzy; Nowakowski, Andrzej (Instytut Historii Kultury Materialnej Polskiej Akademii Nauk, 1981)
23 cm
Keywords: history of material culture

Preface - Maik, Jerzy; Słupecki, Leszek P. (Institute of Archaeology and Ethnology of Polish Academy of Sciences, 2015)
29 cm
Keywords: archaeology -- journals; history -- journals

Masowe i importowane tkaniny z wykopalisk w Kruszwicy - Cybulska, Maria; Hanc-Maik, Ewa; Maik, Jerzy (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2022)
ill.

Tekstylia z cmentarzyska kultury wielbarskiej w Malborku-Wielbarku, stan. 1 (5) - Maik, Jerzy; Łuczkiewicz, Piotr; Kleemann, Jörg (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The cemetery at Malbork-Wielbark was excavated in 1927–1936, 1984–1985 and 2008–2021. All in all, more than 2200 burials were discovered, dated from phase A1 of the younger pre-Roman period through the Migration period (phase D1). Remains of 12 textiles and one piece of thread were found in nine of the graves, most of them recently excavated. The textiles were very poorly preserved, surviving mostly because of proximity with metal artifacts. They were either linen tabbies or woolen 2/2 twills, both typical in Wielbark Culture territory and more broadly, in central and northern Europe.
ill. ; 24 cm
Keywords: textiles; Wielbark Culture; cemetery; Malbork-Wielbarka

Zastosowanie chromatografii cieczowej w badaniach barwników tkanin zabytkowych - Biesaga, Magdalena; Donten, Mikołaj; Maik, Jerzy; Wach, Anna (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2004)
ill. ; 23 cm
Keywords: history of material culture